SINDROM DOWN PADA ANAK DITINJAU DARI SEGI BIOMEDIK DAN PENATALAKSANAANNYA - Irdawati, Irdawati; Muhlisin, Abi (Jurnal Berita Ilmu Keperawatan, 2009)
Children with Down syndrome are individuals detected from the phenotype (typical clinical symptoms) and have limited intelligence; it is caused by the number of the 21 chromosome is over. This overload number results in homeostasis change encouraging the physical and central nervous system deviance growth. The growth of IQ of the children with Down syndrome can be stimulated by stimulating therapy that is by training the motorist movement since the early child. Through the motorist movement, the nervous growth is stimulated so that it can influence the nerve and brain growth. Games are needed in childhood including the children with Down syndrome, because by having games, it can support their understanding of life.